ANALISIS KONTRIBUSI PAJAK PENGAMBILAN DAN PEMANFAATAN AIR BAWAH TANAH TERHADAP PENDAPATAN ASLI DAERAH PROPINSI SULAWESI SELATAN - Ridwan Ridwan (AkMen JURNAL ILMIAH, 2010)
These results indicate that the development of Tax Revenue Collection and Utilization of Ground Water year 2005-2009 budget has fluctuated from year to year. Contribution of Tax Collection and Use of Underground Water of Revenue (PAD) starting from year 2005-2009 budget is still relatively small at less than 1%, this amount also decreased from year to year because there are no significant revenue growth.